THE ROLE OF SCHOOL REGULATIONS IN IMPROVING STUDENT DISCIPLINE IN GRADE X AT SMKN 3 RANTAU UTARA - Tresna Noni Bekris Harefa; Mila Nirmala Sari Hasibuan; Agus Anjar; Junita (SOSIOEDUKASI, 2026)
This study aims to describe the role of school regulations in improving the discipline of tenth-grade students at SMKN 3 Rantau Utara. A qualitative descriptive approach was employed with purposive sampling, involving the vice principal, one Civic Education teacher, and six students from the Culinary and Fashion departments. Data were collected through classroom observations, semi-structured interviews, and documentation, and analyzed using Miles and Huberman’s interactive model with triangulation to ensure validity. The findings reveal that school regulations contribute significantly to disciplined behavior by fostering responsibility, consistency, and self-awareness. In the classroom, regulations encourage punctual attendance, attentiveness, timely completion of assignments, and readiness of learning equipment. Outside the classroom, they guide the use of break time and environmental cleanliness, although students often prefer leisure activities. At home, discipline remains inconsistent, as students tend to study only when assignments or examinations are approaching. These results highlight that school regulations are not merely administrative rules but serve as instruments of character education aligned with the Pancasila Student Profile. The study emphasizes the importance of collaboration between schools and families to strengthen discipline beyond the classroom and recommends integrating reflective and value-based practices to sustain student responsibility and character formation.